Biopesticides: Use of Rhizosphere Bacteria for Biological Control of Plant Pathogens - Sindhu, Satyavir S; Sehrawat, Anju; Sharma, Ruchi; Dahiya, Anupma (Defence Life Science Journal, 2016)
The pesticides used to control pests and diseases are also implicated in ecological, environmental and human health hazards. To reduce the deleterious effects of these agrochemicals, certain antagonistic microorganisms have been characterised from rhizosphere of different crop plants that suppress various plant diseases and thus, minimize the use of pesticides. The application of these specific antagonistic microorganisms in biological control of soilborne pathogens has been studied intensively in the last two decades. These beneficial rhizosphere microorganisms inhibit the pathogenic bacteria and fungi by producing antibiotics, bacteriocins, siderophores, hydrolytic enzymes and other secondary metabolites. The efficiency of these biocontrol products can be improved by manipulation of the environment, using mixtures of beneficial organisms, physiological and genetic enhancement of the biocontrol mechanisms, manipulation of formulations and integration of biocontrol with other alternative methods that provide additive effects. These biocontrol agents could be effectively utilised in sustainable agriculture for improving growth of crop plants.